2018
DOI: 10.1161/atvb.38.suppl_1.158
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 158: Indoleamine 2,3-dioxygenase 1 is Expressed in Macrophages in Human Coronary Atherosclerotic Plaque and is Associated With Tissue Factor Expression in Activated THP-1 Macrophages

Abstract: Background: Recently, several clinical studies have found that changes in the kynurenine (Kyn) pathway of tryptophan (Trp) metabolism are associated with cardiovascular events. Indoleamine 2,3-dioxygenase 1 (IDO1) is a rate-limiting enzyme of the Kyn pathway and is induced by cytokines, particularly IFNγ. However, the roles of the Kyn pathway on vascular wall thrombogenicity remain unknown. Objective: The present study aimed to localize IDO1 in human co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Consistently, inhibition of IDO or AHR decreases tissue factor expression in macrophages. 87 It was shown that kynurenine but not 3-hydroxyanthranilic and quinolinic acids could induce tissue factor expression in macrophages in the presence of an IDO inhibitor. 88…”
Section: Kynurenine Pathway and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, inhibition of IDO or AHR decreases tissue factor expression in macrophages. 87 It was shown that kynurenine but not 3-hydroxyanthranilic and quinolinic acids could induce tissue factor expression in macrophages in the presence of an IDO inhibitor. 88…”
Section: Kynurenine Pathway and Atherosclerosismentioning
confidence: 99%
“…Consistently, inhibition of IDO or AHR decreases tissue factor expression in macrophages. 87 It was shown that kynurenine but not 3-hydroxyanthranilic and quinolinic acids could induce tissue factor expression in macrophages in the presence of an IDO inhibitor. 88 These findings suggest that the kynurenine pathway is a compensatory mechanism that is activated in atherosclerosis and attempts to protect against atherosclerosis.…”
Section: Kynurenine Pathway and Atherosclerosismentioning
confidence: 99%